PROSES BERPIKIR MAHASISWA DALAM MENYELESAIKAN SOAL KALKULUS - Siti Rochana (Universitas Muhammadiyah Ponorogo, 2018)
This study aims to describe and know the thinking processes of students in menyesikan math problems. The subjects taken in this study are divided into three (3) categories with high, medium, and low mathematical skills in solving calculus problems. The method used is qualitative method which refer to written test and interview. From the results of these studies, respectively obtained the conclusion that students with low ability, moderate, and high have the process of thinking computational thinking, semi-conceptual thinking, and conceptual thinking.Keywords: Process of thinking, calculus